Analgesia Epidural Thorakal sebagai Tatalaksana Terkini Pankreatitis Akut - Cokorda, Padmi (Jurnal Komplikasi Anestesi, 2025)
Acute pancreatitis has high morbidity and mortality rates, especially in moderate to severe conditions. The incidence of this disease reaches 5-30 per 100,000 population per year. The pathophysiology of acute pancreatitis is known to result from microcirculatory dysfunction in the pancreas. Severe abdominal pain is one of the symptoms most frequently complained of by patients, reaching 95%. Complaints of abdominal pain are more severe in the early phase, so multimodal analgesia is needed. Thoracic epidural analgesia is known to provide adequate pain control in 87.5 – 100% of patients. Several experimental studies and clinical data support the use of epidural analgesia in cases of acute pancreatitis. Epidural analgesia provides potential benefit in patients with acute pancreatitis in improving pancreatic perfusion. In thoracic epidural analgesia, sympathetic segmental block occurs which is a way to increase the neural supply to the splanchnic circulation resulting in vasodilation and increased blood flow. This technique is safe to use in patients with acute pancreatitis, but requires adequate hemodynamic monitoring to prevent undesirable events such as hypotension and infection. Key words: pancreatitis, thoracic epidural analgesia, abdominal pain